Geografia: espacialização e comercialização do fenômeno da morte no espaço urbano de Boa Vista-RR - Santos, Raiane Pereira dos (Universidade Federal de Roraima, 2018)
Within a capitalist system society has learned to turn almost everything into commodities or commodities. In this context, space becomes a valuable commodity, since its production depends on speculatory actions of several agents, with interests of public or private order. These agents produce, appropriate and consume this space that we call urban. Entrepreneurs (one of the promoters of space) carry out productive activities that give them forms and, included in this production process, carry out profitable activities. Thus, they transformed death into a product, consolidating a peculiar trade, adding to its symbolic representation an economic sense. Therefore, the present dissertation consists of investigating the commercialization of death in the urban space of Boa Vista / RR, considering the agents that are part of this universe. In order to constitute a theoretical framework, we initially sought to understand human finiteness based on symbolic perception,that is, describing its meaning for the man of the past and the present, in order to make a connection of constitutive approaches. A priori, a history of the western culture was traced before the death, considering its different senses from the middle Ages arriving at the contemporaneity. The investigation took place within the urban space of Boa Vista in which its spatial production was considered. Agents that deal with death have been mapped out, considering the participation of each one within the scope of the research (social and / or economic event), as well as strategic location issues, mainly of the agents that attenuate the sale of products and services. Another moment of approach is to show the socioeconomic relationship that comes from death among the participants and, finally, to emphasize the consolidated trade by the funeral industry. To reach the proposed methodological procedures were used as bibliographical research and field work that included the application of questionnaires and interviews. This research revealed that the city, as a space that has been gradually expanding, has become suitable for investments of this type of business and within this scope funeral companies gain more highlights. However, even with great regret is the family, which "feeds" and "fortifies" all this trade by valuing the symbolic meaning of death.